Embryoid research calls for reassessment of legal regulations - Hengstschläger, Markus (Stem Cell Res Ther, 2021)
It is known that in countries, in which basic research on human embryos is in fact prohibited by law, working with imported human embryonic stem cells (hESCs) can still be permitted. As long as hESCs are not capable of development into a complete human being, it might be the case that they do not fulfill all criteria of the local definition of an embryo. Recent research demonstrates that hESCs can be developed into entities, called embryoids, which increasingly could come closer to actual human embryos in future. By discussing the Austrian situation, we want to highlight that current embryoid research could affect the prevailing opinion on the legal status of work with hESCs and therefore calls for reassessment of the regulations in all countries with comparable definitions of the embryo.